Anti-quorum sensing, antibiofilm, and antibacterial activities of extracts of Centella asiatica L. leaves, and in vitro derived leaves-calli through tissue culture: a potential for biofouling-prevention. Issue 7 (9th August 2022) - Khan, Mo Ahamad; Khan, Haris M.; Ganie, Irfan Bashir; Kumar, Sachin; Shahzad, Anwar; Celik, Ismail; Shahid, Mohammad
Abstract: Extracts of Centella asiatica leaves (LEs), and in-vitro leaf-calli (CEs), were investigated for antibacterial, antibiofilm, and anti-quorum sensing activities. Ethyl acetate extracts from leaves (EALE), leaf-calli (EACE), methanolic extracts from leaves (MELE), and leaf-calli (MECE) showed antibacterial activity; the minimum inhibitory concentrations (MICs) of LEs and CEs ranged from 0.312–2.50 mg ml −1 and 0.625 − 2.50 mg ml −1, respectively. The MICs of EALE and EACE were 2.50 mg ml −1, each, for C. violaceum 12742, and P. aeruginosa PAO1. At sub-MIC levels, EALE and EACE showed anti-quorum sensing (anti-QS) activity, demonstrated by concentration dependent pigment inhibition of C. violaceum 12742. Similarly, EALE and EACE inhibited QS-controlled virulence factors in P. aeruginosa PAO1 (biofilm, pyocyanin, and pyoverdin); again, the inhibition was concentration-dependent. The best effect was at immediate sub-MIC concentration i.e. 1250 µg ml −1 . GC-MS analyses revealed the presence of compound 9, 12-Octadecadienoic acid, and in silico docking study suggested interactions with QS-receptors CviR', LasI, and LasR proteins for anti-QS activity.